2019
DOI: 10.1002/jsfa.9554
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of abscisic acid and nitric oxide on chilling resistance and active oxygen metabolism in peach fruit during cold storage

Abstract: Background Cold conditions can accelerate the production of reactive oxygen species (ROS), and excessive ROS may attack biological macromolecules, disrupt related signal pathways, induce oxidative stress and influence plant metabolism. The cross‐talk between nitric oxide (NO) and abscisic acid (ABA) and the inhibitions by NO or ABA on oxidative damage have been reported in fruits. However, there are few reports about the roles of NO–ABA interactions in chilling stress and antioxidant defense in fruits during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Exogenous ABA can induce NO generation in Arabidopsis , which is consistent with the results in peach fruits during storage. We found that NO can regulate the activation of antioxidant activity induced by ABA in peaches during cold storage and increase plant adaptive responses to cold stress . In the present study, ABA mediated the biosynthesis of NO through the NR pathway.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Exogenous ABA can induce NO generation in Arabidopsis , which is consistent with the results in peach fruits during storage. We found that NO can regulate the activation of antioxidant activity induced by ABA in peaches during cold storage and increase plant adaptive responses to cold stress . In the present study, ABA mediated the biosynthesis of NO through the NR pathway.…”
Section: Discussionsupporting
confidence: 58%
“…Similarly, exogenous ABA application increased ABA levels and improved sugarcane cold resistance . These results may be helpful for reducing the CI of fruits during cold storage …”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations